1993
DOI: 10.1038/362219a0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of globular domain of histone H5 and its implications for nucleosome binding

Abstract: The structure of GH5, the globular domain of the linker histone H5, has been solved to 2.5 A resolution by multiwavelength anomalous diffraction on crystals of the selenomethionyl protein. The structure shows a striking similarity to the DNA-binding domain of the catabolite gene activator protein CAP, thereby providing a possible model for the binding of GH5 to DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
593
0
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 746 publications
(614 citation statements)
references
References 41 publications
15
593
0
6
Order By: Relevance
“…However, the fact that the globular domain of H1 alone provided the majority of the observed repression (Fig. 1) indicates that repression is largely mediated by the binding of the globular "winged helix" structure (41). Indeed, the observation that H1 binding to reconstituted nucleosome cores is dependent on the presence of linker DNA (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…However, the fact that the globular domain of H1 alone provided the majority of the observed repression (Fig. 1) indicates that repression is largely mediated by the binding of the globular "winged helix" structure (41). Indeed, the observation that H1 binding to reconstituted nucleosome cores is dependent on the presence of linker DNA (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Analysis with the software DALI 40 showed that only the N-terminal portion of the structure -that is, the helix core and the β-hairpin arm -bears minor similarity to the globular domain of histone H5 (Z-score 5.3) 41 . The structure of the globular domain of histone H5 belongs to the superfamily of winged-helix DNA binding proteins.…”
Section: Overall Fold Of the Dep Domain Of Mdvl1mentioning
confidence: 99%
“…Chromatin opening by FoxA in vitro does not require ATP or ATP-dependent chromatin remodelers (Cirillo et al 2002). Notably, the DNA-binding domain of FoxA resembles that of linker histone and binds to one side of a DNA helix along the long axis of DNA, which leaves the other side of DNA to bind core histones (Clark et al 1993;Ramakrishnan et al 1993;Cirillo et al 1998). Thus, the FoxA pioneer factor is structurally suited to recognize its DNA target sites on a nucleosome.…”
Section: The Basis For Pioneer Activity: Nucleosome Binding and Chrommentioning
confidence: 99%